Financial cost of amyotrophic lateral sclerosis: A case study. Issue 1 (March 2015) - Obermann, M.; Lyon, M.
Abstract: There are only a few recently published reports of the cost of amyotrophic lateral sclerosis (ALS) care in the United States. Our objectives were to: 1) report annual and disease-duration costs; 2) provide costs related to specific care and services; 3) present costs by payor; and 4) identify strategies and resources that can be offered to patients to assist with the financial burden of ALS. Over a 10-year period (2001–2010), all expenses related to the cost of care for an individual patient were collected concurrently and then analyzed in 2012. Results showed that total disease-duration costs were 1, 433, 992 (85% paid by insurance, 9% paid by family, 6% paid by charities). The highest costs were for in-home caregivers (669, 150), ventilation (212, 430) and hospital care (114, 558). In conclusion, this case study illustrates costs of care for ALS as a burden for patients that may impact treatment decisions. Charity organizations and insurance case-managers provide services to patients that can help reduce this burden. Costs for specific services as well as resources identified by this study offer physicians and other healthcare providers data-based cost of care information and strategies to share with their patients.